2016
DOI: 10.4236/health.2016.813139
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge Level and Self-Reported Attitudes of Food Handlers: Case Study of a University Campus

Abstract: This study was performed conducting surveys to assess the Knowledge Level (KL) and Self-Reported Attitudes (SRA) of Food Handlers (FH) in order to evaluate their food safety perception. Food handlers working in 5 cafes and 6 canteens in a university campus responded to a questionnaire about food hygiene. The knowledge level about food hygiene was obtained by answering five question groups (G): Agents involved in food borne diseases (G1), Food handling hygiene (G2), Cross contamination (G3), Heat treatment/cool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…Studies conducted by Byrd-Bredbenner et al. (2013) and Soares et al. (2016) highlighted the same findings where their participants do not use the appropriate temperature requirement for foods when storing, preparing, or bringing them to the customers.…”
Section: Resultsmentioning
confidence: 89%
“…Studies conducted by Byrd-Bredbenner et al. (2013) and Soares et al. (2016) highlighted the same findings where their participants do not use the appropriate temperature requirement for foods when storing, preparing, or bringing them to the customers.…”
Section: Resultsmentioning
confidence: 89%
“…1 It is generally believed that knowledge and practice of basic food hygiene could contribute significantly to prevention and control of food borne diseases and thus significantly reduce adverse human health and economic burden associated with food borne diseases. 12,13 It has been shown that food handlers who had good knowledge of food hygiene were more likely to have better food handling practices compared to those who had poor knowledge. 14 While knowledge is a prerequisite for positive attitudes and practices, there are many other factors such as environmental, social, cultural, belief systems, and so on, that contribute to determining whether knowledge of handling food properly positively impacts attitude and practices in the workplace.…”
mentioning
confidence: 99%